Submersions of Contact CR-Submanifolds of Generalized Quasi Sasakian Manifolds. Issue 1 (2nd January 2020) - Siddiqi, Mohd Danish
Abstract: In this paper, we discuss some properties of almost contact metric submersion of contact CR -submanifolds of generalized quasi-Sasakian manifold and derive some results based on their curvatures's differential geometry. We also study de-Rham cohomology of CR -submanifold of generalized quasi-Sasakian manifold under the submersion.